The effect of intravenous paracetamol infusion on postoperative nausea-vomiting and pain following strabismus surgery in children- a randomised controlled trial - Hulya Gundogdu; Zeliha Korkmaz Disli; Nalan Ornek Celebi (Medicine Science, 2022)
Strabismus surgery is associated with postoperative nausea-vomiting (PONV) and pain. In this prospective-randomized trial we aimed to investigate the effects of intra-operative paracetamol infusion on postoperative nausea-vomiting and pain following strabismus surgery in children. Following approval of ethical committee 50 pediatric patients aged between 3-12 physical status of ASA I-II (American Society of Anesthesiology) undergoing strabismus surgery are included in the study between 2012 and 2013 years. Patients were excluded from the study for these following reasons: known allergic history to paracetamol or other non-steroidal anti-inflammatory drugs (NSAID), morphine and other drugs used in the study; asthma; liver or kidney dysfunction and bleeding disorders. Patients were randomized into two following groups: intravenous paracetamol and IV morphine. Demographic data were similar among groups. Nausea, vomiting scales and anti-emetic requirement of the groups were compared at 0.min, 30.min, 2 hrs and 24 hrs. Analysis had shown that there is a significant difference at the 30th minute, there were no significant differences at other time periods. Wong-Baker faces pain rating scale were compared between groups at 0.min, 30.min, 2 hrs and 24 hrs and no significant differences were seen between group (p > 0.05). Analgesic requirement and sedation scores were compared between groups at 0 min, 30 min, 2 hrs and 24 hrs and no significant differences were seen between groups (p < 0.05). It can be concluded that intravenous paracetamol infusion can safely be used as a replacement to opioids in children undergoing strabismus surgery. [Med-Science 2022; 11(2.000): 496-501]